2012
DOI: 10.1002/chem.201201812
|View full text |Cite
|
Sign up to set email alerts
|

Efficient NIR‐Light Emission from Solid‐State Complexes of Boron Difluoride with 2′‐Hydroxychalcone Derivatives

Abstract: This article describes a series of nine complexes of boron difluoride with 2'-hydroxychacone derivatives. These dyes were synthesized very simply and exhibited intense NIR emission in the solid state. Complexation with boron was shown to impart very strong donor-acceptor character into the excited state of these dyes, which further shifted their emission towards the NIR region (up to 855 nm for dye 5 b, which contained the strongly donating triphenylamine group). Strikingly, these optical features were obtaine… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
60
0

Year Published

2013
2013
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 92 publications
(62 citation statements)
references
References 68 publications
2
60
0
Order By: Relevance
“…They possessed many interesting properties that were suitable for applications in materials science as unique solid-state NIR fluorophores. 44 Shao et al reported a new class of NIRF dendrimeric quaterrylenediimide dyes exhibiting high photostability and hydrophilicity International Journal of Nanomedicine 2014:9 submit your manuscript | www.dovepress.com…”
Section: Nirf Probes Based On Other Types Of Dyesmentioning
confidence: 99%
“…They possessed many interesting properties that were suitable for applications in materials science as unique solid-state NIR fluorophores. 44 Shao et al reported a new class of NIRF dendrimeric quaterrylenediimide dyes exhibiting high photostability and hydrophilicity International Journal of Nanomedicine 2014:9 submit your manuscript | www.dovepress.com…”
Section: Nirf Probes Based On Other Types Of Dyesmentioning
confidence: 99%
“…The data are collected in Table 1. Like the case of 1, [1] the electronic absorption spectra of 2 and 3 in DCM (Figure 1) display an intense lowest-energy transition band located between 450 and 480 nm. The maximum absorption of 3 is at a longer wavelength compared to 1, which may be due to the presence of two electron donor groups on the A ring.…”
Section: Uv-vis and Fluorescence Emission Properties In Solutionmentioning
confidence: 78%
“…For the three compounds investigated, we obtained weak values of Φf in DCM (< 2 %) which shows that non radiative deactivation pathways, such as intramolecular rotation processes, are very efficient within those dyes. [1] …”
Section: Uv-vis and Fluorescence Emission Properties In Solutionmentioning
confidence: 99%
See 2 more Smart Citations